Prediction and optimizing residual stress profile induced by cold expansion in aluminum alloys using experimental design - M. Laredj; A. Miloudi; A. Lousdad; M. Benguediab (Fracture and Structural Integrity)
Cold expansion by hardening is a common process used in the aerospace industry to extend the fatigue lifetime of drilled assemblies due to the existence of a field of high compressive tangential residual stresses. The understanding and the control of the residual stresses are thus important, since it can be beneficial to improve the reliability and lifetime of the structures. The main objective of this work is to establish and validate a predictive model of residual stresses generated by cold hardening. This technique will be useful for industrial application since it allows the estimation of the fatigue lifetime of parts with respect to the process parameters. This tool can also be used to determine the optimal parameters in order to maximize the fatigue lifespan. An experimental setup was used to highlight the effect of the expansion degree, the thickness of the part and the yield strength on the residual stresse profiles. Moreover, the proposed mathematical models are used to determine the optimal values of the process parameters and predict the residual stress in order to achieve a maximum service life of cracked structure after repair. Also it aims to delay crack initiation and growth in riveted or bolted structures. Moreover, the modelling allows to highlighting the effect of these factors and their interactions on the residual stresses profiles.